FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PADA PERUSAHAAN LOGAM DAN SEJENISNYA - Agustina, Leny; Solikah, Mar’atus; Widiawati, Hestin Sri (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose of this study was to examine the effect of receivables turnover, liquidity, solvency, and firm size on the financial performance of the metal business and related products listed on the IDX, either separately or simultaneously. This study uses a quantitative methodology and multiple linear regression analysis with SPSS version 23. Based on the results of the study, accounts receivable turnover, solvency, and firm size partially have no effect on the company's financial performance, while liquidity partially has a significant effect. Furthermore, accounts receivable turnover, liquidity, solvency, and firm size all have an impact on financial performance at the same time. This research is focused on the metals sub-sector and related sub-sectors and uses the latest data for 2018 to 2021.